The taxonomy of Indian gorgonians: an assessment of the descriptive records of gorgonians (Anthozoa: Octocorallia: Alcyonacea) recorded as occurring in the territorial waters of India, along with neighbouring regions and the Andaman and Nicobar Islands, and the highlighting of perceived unethical practice - Ramvilas, Ghosh; Alderslade, Philip; Ranjeet, Kutty (Zootaxa, 2023)
The descriptive taxonomic records of a total of 226 gorgonian species (Octocorallia: Alcyonacea) from Indian seas and neighbouring areas were surveyed and critically reviewed with the main aim of providing a more reliable checklist. The published accounts comprise: species originally described from within the region: subsequent descriptive records of the taxa originally described from within the region; and subsequent descriptive records of species originally described from outside of the region. The reviews include an attempt to assess the validity of all subsequent descriptive records, although in numerous cases the species have been assessed as unrecognisable from their type descriptions. Numerous new binomial combinations, some tentative, have been proposed. The assessment of the validity of a species record is expressed as an “Opinion” with supporting justification. Of the 226 species, there are 111 that were originally described from locations outside of Indian waters and have subsequently been described and recorded as occurring in the region. Of these, there are 9 species where we were unable to decide if the records are valid or not, 94 were assessed as invalid, 5 as possibly valid and 3 were considered valid. The survey highlights four major problems regarding the reliability of some more recently published taxonomic records for the region: the use of ‘predatory journals’; plagiarism; the use of manipulated imagery in more than one description; and taxonomic decision apparently based on expediency.